2017
DOI: 10.3389/fpsyg.2017.00509
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lausanne Trilogue Play in Three Cases of Gastroschisis Diagnosed during Pregnancy

Abstract: From pregnancy to the 1st years of a child’s life, families develop and increase representations and interactive competences toward the child. Prenatal diagnosis of a severe fetus’ defect could profoundly alter the parental perception and development of these representations. The aim of the study was to evaluate triadic interactions in families, whose baby was prenatally diagnosed with severe gastroschisis. Three families took part in the preliminary case study, which was carried out when the babies were 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…LTP studies confirmed the association between peculiar relational patterns and some traits of developmental psychopathologies, such as emotional difficulties, externalizing and internalizing problems o n l y (Gatta et al, 2015;Gatta et al, 2017b;Mazzoni, Lavadera, Di Benedetto, Criscuolo & Mangano, 2015), infantile anorexia (Lucarelli, Ammaniti, Porreca, & Simonelli, 2017), and autistic spectrum disorder (Mazzoni, Veronesi & Vismara, 2013). The quality of triadic interactions changes in association with child's medical condition (Gatta et al, 2017c;Pellizzoni, Tripani, Miscioscia, Giuliani, & Clarici, 2017), and can promote better child outcomes in situations of parental psychopathology and dyadic parent-child dysfunctional interactions (Tissot, Favez, Frascarolo & Despland, 2016). Given the above considerations, in 2012 we started a longitudinal research project based on the cooperation between the Mental Health Unit for Children and the University of Padua.…”
Section: Introductionmentioning
confidence: 99%
“…LTP studies confirmed the association between peculiar relational patterns and some traits of developmental psychopathologies, such as emotional difficulties, externalizing and internalizing problems o n l y (Gatta et al, 2015;Gatta et al, 2017b;Mazzoni, Lavadera, Di Benedetto, Criscuolo & Mangano, 2015), infantile anorexia (Lucarelli, Ammaniti, Porreca, & Simonelli, 2017), and autistic spectrum disorder (Mazzoni, Veronesi & Vismara, 2013). The quality of triadic interactions changes in association with child's medical condition (Gatta et al, 2017c;Pellizzoni, Tripani, Miscioscia, Giuliani, & Clarici, 2017), and can promote better child outcomes in situations of parental psychopathology and dyadic parent-child dysfunctional interactions (Tissot, Favez, Frascarolo & Despland, 2016). Given the above considerations, in 2012 we started a longitudinal research project based on the cooperation between the Mental Health Unit for Children and the University of Padua.…”
Section: Introductionmentioning
confidence: 99%